ANALISIS KEKUATAN PIPA GLASS-FIBER REINFORCED EPOXY TERHADAP BEBAN IMPAK, BEBAN TEKUK, DAN BEBAN TEKAN DI JOB PERTAMINA-PETROCHINA EAST JAVA - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
This study aims to determine the strength of the pipe Glass-fiber Reinforced Epoxy due to impact load, bending load, compression load and be able to analyze the failure potential of the shear stress on the pipe inner wall due to the fluid flow in it. Some test has been done, there are impact test with notched Charpy method (ISO 179-10), 3-point bending test (ASTM D 790-15), and the compression test (ASTM D 695-15). Volume fraction of Glass-fiber Reinforced Epoxy pipe for the Glass-fiber (E-glass) is ± 72.85% and for the Epoxy (Bisphenol A) is ± 27.15%. The orientation angle is 54.75 (continued) and the pipe was made by the helical filament winding method. The test results showed the impact strength is 190.10 ± 20.95 kJ / m2, the bending strength is 115.16 ± 5.50 N / mm2, and the compression strength is 259.48 ± 11.85 N / mm2. It is much larger than the calculation of shear stress on the wall of the pipe that assumed. In other word the pipe is safe from failure potential of the shear stress on the pipe inner wall due to the fluid flow in it.